Corporal punishment and reporting to child protection authorities: An empirical study of population attitudes in five European countries. (January 2021) - Burns, Kenneth; Helland, Hege Stein; Križ, Katrin; Sánchez-Cabezudo, Sagrario Segado; Skivenes, Marit; Strömpl, Judit
Highlights: Significant cross-country differences in attitudes towards Corporal Punishment. Small differences between countries in attitudes towards reporting Corporal Punishment. Differences between countries may be due to populations trust in government. Abstract: This study, which draws upon representative survey data of the populations of Austria (n = 1000), Estonia (n = 1069), Ireland (n = 1000), Norway (n = 1002) and Spain (n = 1000), compares population attitudes towards corporal punishment (CP) and whether citizens would report corporal punishment to the child protection authorities. We found significant cross-country differences in attitudes towards CP, but only small differences between countries in attitudes towards reporting it. The most interesting and puzzling finding was the mismatch between attitudes towards CP and attitudes towards reporting it: almost one third of individuals who reject CP would not report it, and a quarter of those accepting CP would report it. We discuss whether the observed mismatches are due to perceptions that the CP we described does not meet a threshold to require state intervention, and whether knowledge about bans of CP and/or moral obligations to report CP has impact. Furthermore, we discuss the role of populations' confidence in the state and populations' trust in the ability and competency of the child protection authorities to improve a child's life.